الضغوط المهنية وعلاقتها بالاضطرابات السيكوسوماتية لدى الاساتذة - عبد الغني مخلوفي; عبد الرحمان حمدي; لبصير سفيان (My University, 2023)
This study aimed to reveal the relationship between occupationalstress and psychosomatic disorders among teachers, and to achieve this, we followed the steps of the descriptive approach as it is the appropriate approach for the subject. We also used two tools to collect information and data represented in the Psychological Stress Scale and the Cornell Psychosomatic Disorders Scale, and after verifying the psychometric characteristics of honesty and stability, the obtained data were processed statistically based on the spss20 program, and after analyzing the results, this study reached the following results: 1There is a positive correlation between occupational stress and psychosomatic disorders among teachers 2There is a positive correlation between occupational stress and psychosomatic disorders among teachers, according to the controlling variable of age 3There is a positive correlation between occupational stress and psychosomatic disorders among teachers, according to the controlling variable of seniority in work key words: Occupational Stress, psychosomatic disorders, the teache